Desain Jalan Tambang PT. Vale Indonesia Tbk Sorowako - Anwar, Habibie; Thamsi, Alam Budiman (CV Insight Publisher, 2024)
The main function of the mine road is to support the smooth of mining operation, especially in transportation activities, so the good mine road is necessary to design to improve hauling productivity. This research aimed to determine the ideal road geometry for the transportation activities. The data used in this research are topography map, transportation equipment specification data, SOP (standard operational procedure) of road design, and road geometry data. Data processing is conducted to make the calculation of road geometry using rational formula, then based on the result of the calculation, the design of mining road is made. The results of the research showed that the minimum road widths for the straight road are 22 m and for the bend are 28 m, then have the grade of 10% or 3.6°, have the cross slope with height of 3%, and for the bend with width 28 m. The good superelevation used is 6% m. In conclusion, the geometry of mine road at PT. Vale Indonesia, Tbk has been the ideal for fulfilling the hauling activities.